Teaching Physiotherapy Students Physical Examination Skills by Using Photogrammetry: A Randomized Control Trial of 3- Versus 2-Dimensional Images. Issue 1 (February 2022) - Lo, Chi Ngai; Abdelkader, Tarek; Choi, Yik Ming; Goff, Anthony James; Suresh, Krishnasamy; Carpio, Guiller Augustin Cea; Soon, Benjamin
Abstract : Introduction: Education research explains how healthcare professional training could be more efficient and effective by integrating simulation technology. Despite its relevance in training medical students, the evidence of its effectiveness in the manual skill training of physiotherapy students remains limited. The aim of this study was to compare the effectiveness of 3-dimensional (3D) images of real objects produced by photogrammetry and traditional 2-dimensional (2D) images when introducing manual therapy skills to undergraduate physiotherapy students via an online course. Methods: In a randomized controlled trial, a group of first-year physiotherapy bachelor honor degree students participated in a 2-hour online course on 3 manual assessment skills: cervical compression, distraction, and flexion-rotation tests. They demonstrated 2 sets of learning materials, including either 3D images of real rotating objects using close-range photogrammetry (experimental group) or traditional 2D images (control group). After their respective training, an Objective Structured Clinical Evaluation procedure was conducted to demonstrate their knowledge about the techniques. A standardized 9-item practical performance test was used as the primary outcome measure for the analyses. Results: Seventy-seven students participated in the study. The average Objective Structured Clinical Evaluation score for the experimental group (n = 40) was 41.3/50 (±3.9) and the control group (n = 37) was 39.1/50 (±4.5, P = 0.02). Conclusions: For learning 3 cervical spine assessment skills, this study shows that photogrammetry creates 3D images of real rotating objects that are more effective than 2D images for first-year physiotherapy students. Abstract : Supplemental digital content is available in the text.